Fear and Challenges of Nursing Students Being in Hospital for Clinical Posting During the COVID-19 Pandemic: An Exploratory Survey - Rana, Nimarta; Kalal, Nipin; Sharma, Suresh K. (Frontiers in Psychology, 2022)
Background The world is facing unprecedented challenges in the face of a global pandemic (COVID-19). The institutions resumed nursing students’ clinical experiences as an earlier part of their curriculum, which was transitioned to a virtually delivered format due to global disaster. Therefore, working through this pandemic in hospital posting is challenging and fearful for nursing students. The aim of this study was to measure the fear of COVID-19 and the challenges faced by nursing students when posted in hospitals during the COVID-19 pandemic. Methods A web-based exploratory survey was conducted on 185 participants from March 2021 to April 2021. Participants were selected through a web-based survey (Google form) by non-probability purposive sampling technique. The Fear of COVID-19 Scale and self-structured questionnaires with the Likert-type scale were used to measure the fear of COVID-19 and the challenges faced by nursing students when posted in hospitals during the COVID-19 pandemic, respectively. Descriptive and inferential statistics were used for the analysis of data with IBM SPSS version 27. Results A significant number (61.1%) of participants had moderate fear of COVID-19 infection, one-third of them (28.1%) had mild fear, and very few participants (10.8%) had an extreme fear of COVID-19 infection. The majority of participants (64.9%) faced moderate challenges, 27% faced high challenges, and very few study participants (8.1%) did not face any challenges when posted in the hospital during the COVID-19 pandemic. The fear due to COVID-19 is not associated with demographic variables, but the challenges faced due to COVID-19 are significantly associated with demographic variables, such as the age, batch, and duration of clinical posting (p-value = 0.01). Conclusion Study data indicated that respondents reported fear of COVID-19 infection and also experienced a variety of challenges in hospital posting during the COVID-19 pandemic.